Motivasi, Kompensasi dan Budaya Organisasi terhadap Kinerja Karyawan - Diah Rahayu; Lie Liana (Journal of Management and Bussines (JOMB), 2023)
This study aims to analyze the effect of motivation, compensation and organizational culture on employee performance at PERUMDA Tirta Bumi Serasi Drinking Water, Semarang Regency. This study uses quantitative research methods and in the analysis process uses multiple linear analysis techniques. The sample used was 82 respondents. Data collection was carried out in this study using a questionnaire which was distributed directly to the respondents. The results showed that motivation had a positive and significant effect on employee performance, compensation had no effect on employee performance, and organizational culture had a positive and significant effect on employee performance. In conclusion, the application of better motivation will have an impact on better employee performance, as well as improving organizational culture, then employee performance will increase. Meanwhile, compensation cannot be a factor to improve employee performance. Keywords: Organizational Culture, Employee Performance, Compensation, Motivation